The Self Regulation Predicts Preschool School Readiness: Regulasi Diri Memprediksi Kesiapan Sekolah pada Anak Usia Prasekolah - Shevia Dwi Puspitasari; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background School readiness is a multidimensional construct encompassing cognitive, social, emotional, physical, and communication competencies required for successful transition to formal education. Specific Background Self regulation, involving cognitive, emotional, and behavioral control, is considered a foundational component of children’s socio emotional development during the preschool period. Knowledge Gap Previous studies have largely examined associations without addressing causal direction or have focused on primary school populations rather than preschool children entering formal schooling. Aims This study aimed to examine the relationship between self regulation and school readiness among preschool children aged 5–6 years in Sidoarjo Regency using a quantitative causal approach. Results Analysis of data from 106 participants using simple linear regression indicated a positive and statistically significant relationship between self regulation and school readiness (F < 0.05), with a contribution of 9.3% and a correlation coefficient of r = 0.306, categorized as low. Most children demonstrated moderate levels of both variables. Novelty The study provides empirical evidence on preschool populations and examines directional association rather than mere correlation, positioning self regulation as a foundational element of readiness for formal schooling. Implications Findings suggest that strengthening children’s ability to manage attention, emotions, and behavior may support smoother adaptation to structured learning environments, although additional factors beyond the present model also contribute to readiness outcomes. Highlights: Most participants demonstrated moderate levels across both measured constructs. Statistical testing indicated a significant positive association with low strength (r = 0.306). The predictor accounted for 9.3% of variance, indicating substantial contribution from other variables. Keywords: Self Regulation; School Readiness; Preschool Children; Early Childhood Education; Socio Emotional Development